K-Ar DATING OF SELECTED IGNEOUS SAMPLES FROM THE SIBOLGA BASIN, MEULABOH AND SIMEULUE ISLAND, WESTERN SUMATRA - Helen J. Kallagher (Testing Center for Oil and Gas LEMIGAS, 1990)
As part of a general study of the sedimentation, structure and tectonic evolution of the northern part of the Sumatranforearc basin samples of igneous rock were collected for K-Ar dating from the eastern margin of the Sibolga Basin, and from the outer arc island of Simeulue.